Challenges and Opportunities for the Renewable Energy Economy - Reboredo, Juan Carlos (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Renewable energy deployment as an alternative to traditional energy sources is the cornerstone of the emission-reduction energy policies that aim to facilitate the transition to a low-carbon economy. This transition poses risks and opportunities for companies with business models that rely directly or indirectly on renewables, which will be reflected in the revaluation of assets and in the reallocation of private and public financial investments from carbon-intensive to low-carbon energies. In a series of selected articles, this book addresses current challenges and opportunities for renewable energies from technological, economic and financial perspectives.